The Effects of Morning Assembly Activities on the Independence Character of Students (Pre-Experimental Designs at SMK Karya Mandiri Nusawungu) - Lisa Selina Nursiyami; Efi Miftah Faridli; Ratna Kartika Wati (UM Purwokerto Press, 2024)
This study aims to determine the extent of morning assembly activities' effects on students' independent character. The method used in this research is Pre-Experimental Designs with a One-Shot Case Study design. The sample comprises 56% or 157 students from the total 10th-grade classes. Data collection techniques employed in this study include observation, interviews, documentation, and questionnaires. The data analysis method utilized is the Partial T-test. The results indicate that morning assembly activities impact the independent character of students at SMK Karya Mandiri Nusawungu. This conclusion is based on the Partial T-test results, which show a calculated T value of 18.043 compared to a table value of 0.67608 and a significance value of 0.000, which is less than 0.05, indicating that morning assembly activities significantly affect the independent character of students. Furthermore, the simple linear regression test results reveal a correlation value of 0.823 or 82.3%, which falls into the very high category. Additionally, the coefficient of determination (R Square) test results show a value of 67.7%, indicating that it is clear that variable X (morning assembly activities) affects variable Y (independent character). The high R Square value demonstrates that morning assembly activities significantly affect students' independent character.